Working Conditions of Venezuelan Immigrants in Cúcuta, Los Patios and La Parada (Colombia): Decent Work? (2023)
Migration processes entail a change in the conditions of the existence of its protagonists as they integrate into a new life, where work is of paramount importance. For this reason, it is interesting to know the working conditions of immigrants when they settle in the new host country, as it is up to the latter to design policies that strengthen their integration, with decent work being relevant, as it has an impact on the well-being of these people, as set out in the great challenge of the Global Compact. Thus, a study was conducted on the working conditions of Venezuelan immigrants settled in the border cities of Cúcuta, Los Patios, and La Parada (Colombia) using a quantitative methodology through a multidimensional analysis of the factors related to their occupation, projecting a perceptual map with similarities and differences that show the characteristics of their current working conditions. These findings made it possible to determine that the current working conditions do not correspond to decent work, which requires the design of proposals by those who manage the governance of migration that favour labour insertion and the achievement of the sustainable development objective of decent work.